Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Certainly! Let's solve the given equation step-by-step:
The equation we are given is:
[tex]\[ 7 + 42 \cdot 3^{2 - 3a} = 14 \cdot 3^{-2a} + 7 \][/tex]
### Step 1: Simplify Both Sides of the Equation
First, let's eliminate the 7 terms on both sides:
[tex]\[ 42 \cdot 3^{2 - 3a} = 14 \cdot 3^{-2a} \][/tex]
### Step 2: Divide Both Sides by the Common Factor
Next, let's divide both sides of the equation by 14 to make it simpler:
[tex]\[ 3 \cdot 3^{2 - 3a} = 3^{-2a} \][/tex]
### Step 3: Use Properties of Exponents
We can rewrite [tex]\( 3 \cdot 3^{2 - 3a} \)[/tex] as:
[tex]\[ 3^1 \cdot 3^{2 - 3a} = 3^{1 + 2 - 3a} = 3^{3 - 3a} \][/tex]
So, the equation now becomes:
[tex]\[ 3^{3 - 3a} = 3^{-2a} \][/tex]
### Step 4: Equate the Exponents
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ 3 - 3a = -2a \][/tex]
### Step 5: Solve for [tex]\(a\)[/tex]
Now we solve the equation for [tex]\(a\)[/tex]:
[tex]\[ 3 - 3a = -2a \][/tex]
Add [tex]\(3a\)[/tex] to both sides:
[tex]\[ 3 = a \][/tex]
So, we have found that:
[tex]\[ a = 3 \][/tex]
### Conclusion
Among the given possible solutions [tex]\(a = -3\)[/tex], [tex]\(a = 0\)[/tex], [tex]\(a = 3\)[/tex], and "no solution", the solution to the equation is:
[tex]\[ a = 3 \][/tex]
Therefore, the valid answer is:
[tex]\[ a = 3 \][/tex]
The equation we are given is:
[tex]\[ 7 + 42 \cdot 3^{2 - 3a} = 14 \cdot 3^{-2a} + 7 \][/tex]
### Step 1: Simplify Both Sides of the Equation
First, let's eliminate the 7 terms on both sides:
[tex]\[ 42 \cdot 3^{2 - 3a} = 14 \cdot 3^{-2a} \][/tex]
### Step 2: Divide Both Sides by the Common Factor
Next, let's divide both sides of the equation by 14 to make it simpler:
[tex]\[ 3 \cdot 3^{2 - 3a} = 3^{-2a} \][/tex]
### Step 3: Use Properties of Exponents
We can rewrite [tex]\( 3 \cdot 3^{2 - 3a} \)[/tex] as:
[tex]\[ 3^1 \cdot 3^{2 - 3a} = 3^{1 + 2 - 3a} = 3^{3 - 3a} \][/tex]
So, the equation now becomes:
[tex]\[ 3^{3 - 3a} = 3^{-2a} \][/tex]
### Step 4: Equate the Exponents
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ 3 - 3a = -2a \][/tex]
### Step 5: Solve for [tex]\(a\)[/tex]
Now we solve the equation for [tex]\(a\)[/tex]:
[tex]\[ 3 - 3a = -2a \][/tex]
Add [tex]\(3a\)[/tex] to both sides:
[tex]\[ 3 = a \][/tex]
So, we have found that:
[tex]\[ a = 3 \][/tex]
### Conclusion
Among the given possible solutions [tex]\(a = -3\)[/tex], [tex]\(a = 0\)[/tex], [tex]\(a = 3\)[/tex], and "no solution", the solution to the equation is:
[tex]\[ a = 3 \][/tex]
Therefore, the valid answer is:
[tex]\[ a = 3 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.